Influence of coloured shade nets and seasons on production and quality of cut foliage of leather leaf fern (Rumohra adiantiformis) - NAIR, SUJATHA A; LAXMAN, R H; SANGAMA, SANGAMA (The Indian Journal of Agricultural Sciences, 2020)
Leather leaf fern [Rumohra adiantiformis (G forst) Ching.] was grown under red, green, white and black coloured shade nets permitting light intensities ranging from 240.50 to 370 μ mol m-2 s-1 (75% shade net), for two consecutive years from 2014-16, at ICAR-IIHR, Bengaluru. The influence of coloured nets and the season on cut foliage yield and quality were evaluated. Developmental stages of the fronds under the different coloured nets were also studied. Fronds attained the harvestable maturity stage at 33 days post emergence under red shade net, whereas it took 31.5 days under green shade net. The plants cultivated under red shade net (75% shade) resulted in higher foliage production/plant/ month (6.60) while it was on par with black shade nets in terms of quality of the foliage with respect to length of lamina (24.90 cm) and frond width (17.77 cm). The vase life of the cut foliage grown under red shade net was 47.6 days. Cultivation of leather leaf fern under red shade resulted in maximum cut foliage yield, quality and post harvest life.